EFEKTIVITAS KOMITE AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan Publik yang Terindikasi Kesulitan Keuangan Tahun 2010-2012) - Firdaus Nikmatullah Akbar; Endang Kiswara (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the impact of audit committee effectiveness on timeliness of financial reporting that indicates financial distress. Audit committee effectiveness are proxied by audit committee expertise, audit committee charter, audit committee size, and audit committee meeting. This study also includes five variable, including ROA, leverage, firm size, accountant public size, and industry type as control variables. The population of this research is the non financial industry companies are listed on the Indonesia Stock Exchange (IDX) 2010-2012 with 76 total samples of non financial companies. Financial distress criteria in this study are measured by cumulative negative earnings over any two years period. Sampling technique used in this research is random sampling method. The result of this study showed that audit committee effectiveness has positive impact on timeliness of financial reporting that indicated financial distress. Audit committee expertise and two control variables are firm size and industry type which has significant and positive impact on the financial reporting that indicated financial distress. Although other variables does not have significant effect on timeliness of financial reporting that indicated financial distress.